Beyond 'deniers' and 'believers': Towards a map of the politics of climate change. (May 2015) - Corry, Olaf; Jørgensen, Dan
Highlights: Categories in climate politics debate are hangovers from climate science debates. Existing frameworks in climate politology are critically reviewed. A new map of climate politics beyond the scientific debate is offered. Two dimensions are proposed: wicked/tame problem and individual/collective solutions. Aims to defuse politicisation of science and re-politicise climate policy choices. Abstract: The politics of climate change is not concerned solely with rival scientific claims about global warming but also with how best to govern the climate. Despite this, categories in climate politics remain caught up in the concepts of the 'science wars', rarely progressing far beyond the denier/believer-dichotomy. This article aims to nudge climate politics beyond the polarized scientific debates while also counteracting the de-politicisation that comes from assuming scientific claims lead directly to certain policies. First existing typologies of climate political positions are reviewed. Diverse contributions make up an emerging field of 'climate politology' but these tend to reduce climate politics either to views on the science or to products of cultural world-views. Drawing on policy analysis literature, a new approach is outlined, where problem-definitions and solution-framings provide the coordinates for a two-dimensional grid. The degree to which climate change is considered a 'wicked' problem on the one hand, and individualist or collectivist ways of understanding political agency on the other, provide a map of climate political positions beyond 'believers' vs 'deniers'.